Hubungan Self Care dengan Kualitas Hidup Pasien Kanker Serviks - Dessy Listya Rissanti (Jurnal Health Sains, 2021)
According to Globocon 2018 data, new cases of cervical cancer reached 32,469 people and the death rate from cervical cancer reached 18,279 per year. This means that about 50 Indonesian women die from cervical cancer every day. This literature study aims to determine the relationship or influence of selfcare on the quality of life of cervical cancer patients. This method of research uses literature riview or literature study method. Article searches are conducted based on keywords from 'Self Care'AND 'Quality of Life'AND 'Cervical Cancer Patients', using pubmed search engine, Google Search Engine (Scholar and Repository) and Researchgate. With the publication of articles from 2015 to 2020. The search results were obtained 11 articles that discuss the topic of self care and quality of life in cervical cancer patients. Published articles published from 2015 to 2020. Each individual has a different quality of life depending on each individual in addressing the problems that occur in him. The use of certain coping strategies can influence their desire for information about their illness, their efficacy, and the way they adjust to the disease and its treatments. The quality of life of cervical cancer patients will improve if we know the supporting factors of a person in performing the treatment of both family support, health workers and social context support so that the patient remains passionate in living his life.